CRACK PREDICTION OF USING FINITE ELEMENT ANALYSIS - Salim, Muhammad Shahrul Izzwan (IRC, 2020)
In current developing world, the use of simulation software has increased rapidly for this past few year. Many fields of study took advantage of simulation software including finance, medical and engineering. The development of simulation software is becoming more advance due to high demand from various industry. In fact, finite element analysis (FEA) are widely used in engineering industry to analyse the behaviour of designed structure element etc. This approximation method is promising a good and reliable results. Thus, the focus of this study is to establish a methodology for prediction of fatigue life (cycles) of a plate with hole in 3-dimensional structured model by using FEA where the data distribution from the FEA will be using for more advanced research.